High-performance silicon-based multicomponent battery anodes produced via synergistic coupling of multifunctional coating layers1. Issue 7 (1st July 2015) - Lee, Jung-In; Ko, Younghoon; Shin, Myoungsoo; Song, Hyun-Kon; Choi, Nam-Soon; Kim, Min Gyu; Park, Soojin
<x xml:space="preserve">Abstract</x> We demonstrate the newly developed Si-based multicomponent anodes exhibiting a highly stable cycling retention (∼65% after 1000 cycles at a 1 C discharge–charge rate).